IN PRAISE OF HER: GENDER, NATION-NESS AND PANEGYRIC, EARLY MANIPRAVALAM AS PERFORMATIVE PRACTICE - PRIYA V. (Samyukta: A Journal of Women’s Studies, 2010)
In this article a reading of early Manipravalam literature of Keralam as a performative practice is attempted. Tracing out from the texts two historical milieus where praise poems in the hybrid tongue were performed, there is a search to read Manipravalams’ objectification of women and the unique nation- ness they evoke for Keralam as two intimately linked and mutually formative constructions imbricated in aesthetic performance that works alongside other less spectacular performances in the medieval society and together enable the consolidation of intricately gendered subjects of caste.